Peningkatan Literasi Digital dalam Pembuatan Karya Tulis Guru Pada Platform Merdeka Mengajar (PMM) - Sari, Ratna; Sari, Rafika; Ramdhania, Khairunnisa Fadhilla; Khalida, Rakhmi; Fitriyani, Aida; Novarizal, Safarin (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
This scientific article aims to evaluate a workshop held at SMP Negeri Satu Atap Cibarusah Bekasi to enhance the digital literacy of teachers. The workshop focused on creating written works in the form of Aksi Nyata Documents on the Merdeka Mengajar Platform (PMM), introducing and utilizing the Canva graphic design application and Gemini Artificial Intelligence to support the writing process. Participants were also trained on the structure of writing Aksi Nyata that meet PMM’s Writing Guidelines to ensure validation, as well as how to provide effective feedback for various types of Aksi Nyata. The workshop consisted of three main sessions: (1) Introduction to the Merdeka Mengajar Platform (PMM), (2) Tips for passing PMM Action Plan validation, and (3) Hands-on practice in creating written works aligned with the theme